DIVERSITY MANAGEMENT IN ORGANIZATIONS: AN INTEGRATIVE SYSTEMATIC REVIEW - Almeida, Ana Paula da Silva; do Amaral, Melissa Ribeiro; Willerding, Inara Antunes Vieira; Lapolli, Édis Mafra (ARACÊ, 2024)
More than merely increasing diversity in the workforce, organizations need to learn how to manage multiple diversities. However, this is a complex challenge that requires appropriate knowledge and strategies. Therefore, this study aims to understand how organizations can implement what diversity management proposes. The methodology included an integrative systematic review, with searches in the Scopus and Web of Science databases, covering the period from 2019 to 2024. This resulted in the selection of 48 articles, which were synthesized and categorized by minority group. The results show that factors such as legislation, organizational culture, and social conditions affect the promotion of diversity. Moreover, human resources practices and inclusive leadership are fundamental to employee satisfaction, especially among minority groups. Organizations that invest in diversity reap benefits such as innovation, improved performance, and talent retention. The findings also revealed that 47.9% of the articles address diversity in a general sense, while those focused on specific markers are predominantly about gender and race or ethnicity. The global relevance of diversity management was also evident, regardless of the organization’s size, sector, or country, with the United States standing out in terms of the volume of empirical research. It is concluded that this study allowed the identification of research that contributes to the adoption of diversity management practices in organizations. For effective diversity management, it is necessary to adopt intersectional and multilevel approaches, considering both internal and external factors.